2023
DOI: 10.3390/ma16072617
|View full text |Cite
|
Sign up to set email alerts
|

Indentation Reverse Algorithm of Mechanical Response for Elastoplastic Coatings Based on LSTM Deep Learning

Abstract: The load-penetration depth (P–h) curves of different metallic coating materials can be determined by nanoindentation experiments, and it is a challenge to obtain stress–strain response and elastoplastic properties directly using P–h curves. These problems can be solved by means of finite element (FE) simulation along with reverse analyses and methods, which, however, typically occupy a lengthy time, in addition to the low generality of FE methodologies for different metallic materials. To eliminate the challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Wang et al [48] employed a hyperparametric tunable artificial neural network model to establish a positive relationship between the material elastoplastic parameters and the indentation P-h curve. Meanwhile, Long et al [49] proposed a long short-term memory neural network to deeply learn the time series of P-h curves to predict the relationship between P-h curves of metal-coated materials and their stress-strain response. This network established the mapping relation from the P-h curves to the corresponding elastoplastic material stress-strain response.…”
Section: Machine Learningmentioning
confidence: 99%
“…Wang et al [48] employed a hyperparametric tunable artificial neural network model to establish a positive relationship between the material elastoplastic parameters and the indentation P-h curve. Meanwhile, Long et al [49] proposed a long short-term memory neural network to deeply learn the time series of P-h curves to predict the relationship between P-h curves of metal-coated materials and their stress-strain response. This network established the mapping relation from the P-h curves to the corresponding elastoplastic material stress-strain response.…”
Section: Machine Learningmentioning
confidence: 99%
“…For these very reasons, the computing speed a computational efficiency of an LSTM model are greatly enhanced. Furthermore, a dropout layer can also be added after each LSTM hidden layer, and its value is usually between 0.2 and 0.5, effectively avoiding the occurrence of overfitting during model training [34,36]. Overfitting is a common problem in deep learning fields [37].…”
Section: Multi-hidden-layer Lstm Structurementioning
confidence: 99%
“…Long short-term memory (LSTM) machine learning algorithms, which can effectively handle sequential data and can learn the long-term dependence of the data [37], have been used to consider time-series features of F-δ curves. However, Long's study [38] revealed that when LSTM networks were used alone for prediction, the results were only acceptable and did not yield the expected excellent results. To solve the above problems, in this paper, a CNN-LSTM architecture combining a convolutional neural network (CNN) and LSTM [39] is used for the first time to estimate TSLs at the bonded interface of IGBT modules.…”
Section: Introductionmentioning
confidence: 99%
“…Long short-term memory (LSTM) machine learning algorithms, which can effectively handle sequential data and can learn the long-term dependence of the data [ 37 ], have been used to consider time-series features of F – δ curves. However, Long’s study [ 38 ] revealed that when LSTM networks were used alone for prediction, the results were only acceptable and did not yield the expected excellent results.…”
Section: Introductionmentioning
confidence: 99%